The Homogeneity of Sŏktok kugyŏl and Hyangch’al and the Principle of Hyangch’al Composition - Kim, Jinhee; Park, Jaemin (Acta Koreana, 2023)
This study compares the hyangch’al of the Silla Kingdom (57 BCE–935 CE) and the Sŏktok kugyŏl of the Koryŏ (918–1392) dynasty. Both hyangch’al and kugyŏl incorporated borrowed characters (ch’aja) from Chinese to phrase the Korean vernacular. Although hyangch’al is older than kugyŏl, materials written in hyangch’al demonstrate a similar usage of borrowed sinographs and analogous syntactic structures. This affinity between the two systems implies they were created in similar cultural contexts by a similar social class. Based on this, the paper reexamines a well-known principle of hyangch’al, called hunju ŭmjong wherein word segments in hyangch’al consist of hunch’a (sinographs borrowed as semantograms) and ŭmch’a (sinographs borrowed for their sound), which together comprise ch’aja or borrowed sinographs. However, the complications inherent to the differentiation of hunch’a and ŭmch’a have led to another crucial division between ch’aja and normal Sinitic being neglected, resulting in a misleading interpretation of hyangch’al. In kugyŏl, a word segment comprises normal Sinitic first followed by sinographs, a rule that also applies to hyangch’al. We call this hanju ch’ajong (Sinitic leads, borrowed usage follows). This paper reclassifies the four categories of hyangch’al characters and applies this reclassification to the reading of hyangga songs recorded in hyangch’al. This approach to utilizing findings from research into kugyŏl allows for a more accurate translation of hyangga songs.
Keywords: ch’aja; hyangch’al; hyangga; interpretation; sŏktok kugyŏl